2015
DOI: 10.1039/c5ta03201f
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized metal–organic framework as a new platform for efficient and selective removal of cadmium(ii) from aqueous solution

Abstract: In this work, we illustrate how to anchor -SO3H functional groups onto the pore surface of MOF for cadmium removal from aqueous solution via the approach of sequential post-synthetic modification and oxidation as exemplified in the context of functionalizing the MOF, Cu3(BTC)2 with sulfonic acid. The resultant sulfonic acid functionalized MOF, Cu3(BTC)2-SO3H demonstrates a high cadmium uptake capacity of 88.7 mg/g, surpassing that of the benchmark adsorbents. In addition, it exhibits a fast kinetics with the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
77
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(79 citation statements)
references
References 48 publications
(50 reference statements)
1
77
0
1
Order By: Relevance
“…Previous study [18] reported that using MOF-808 as adsorbent is efficient at arsenic removal from water. Cu 3 (BTC) 2 -SO 3 H also exhibited high Cd(II) uptake capacity, thus has a potential use for cadmium removal [19]. Other type of MOFs previously used in heavy metals absorption studies were Graphene Oxides (GO) [4], [6], EDTA-Graphene Oxide (EDTA-GO) [3], [20] for Pb(II) removal and MOF-5 [16] and Graphene Oxides-CdS [21] for Cu(II) removal.…”
mentioning
confidence: 99%
“…Previous study [18] reported that using MOF-808 as adsorbent is efficient at arsenic removal from water. Cu 3 (BTC) 2 -SO 3 H also exhibited high Cd(II) uptake capacity, thus has a potential use for cadmium removal [19]. Other type of MOFs previously used in heavy metals absorption studies were Graphene Oxides (GO) [4], [6], EDTA-Graphene Oxide (EDTA-GO) [3], [20] for Pb(II) removal and MOF-5 [16] and Graphene Oxides-CdS [21] for Cu(II) removal.…”
mentioning
confidence: 99%
“…41,42 As shown in Fig. S7, † the obtained zeta potential values of JLUE-COPs decreased with increasing solution pH, and the PZC values were determined to be about 1.0 for JLUE-COP-1 and 1.3 for JLUE-COP-2, respectively.…”
mentioning
confidence: 93%
“…Adsorption has proven to be one of the most effective approaches for the decontamination of polluted water. To date, many kinds of abundant materials have been utilized for removing cadmium, such as polymers, carbon materials, metal–organic frameworks, and composite materials . For example, Wu et al.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Precipitation is ac ommonm ethodb ecause of its high efficiency,b ut it is restricted by secondary pollution,h igh cost, and poor performance with low concentrations of metal ions. [4] Althoughr everse-osmosis systems are cost-effective, they only produce al imited amount of treated water despite using considerable amounts of wastewater.A dsorption has proven to be one of the most effective approaches for the decontamination of polluted water.T od ate, many kinds of abundantm aterials have been utilized forr emoving cadmium, such as polymers, [5] carbon materials, [6] metal-organic frameworks, [7] and composite materials. [8] For example, Wu et al developedakind of aerogel based on graphene oxide to extract cadmium from water and found that the adsorption was attributed to the complexation between the cadmium and sulfog roups of the material.…”
Section: Introductionmentioning
confidence: 99%